Desarrollo de la Medicina Física y Rehabilitación como especialidad médica - Vergara B., Loreto (Revista Hospital Clínico Universidad de Chile, 2010)
Physical medicine and rehabilitation as a medical specialty in the United States emerged in the early 1930’s and was consolidated as such in the early 1950’s, at the same time; it began its development in Europe, together with the establishment of the European Economic Community. Being recognized worldwide in 1968. The White Book of Physical Medicine and Rehabilitation in Europe, published in 1989, covers all areas related to the specialty, from definition to future developments. In Chile, the specialty grew out of the hands of Dr. Livio Paolinelli Monti, who in 1958 completed his studies of Physical Medicine and Rehabilitation at the University of Colorado at Denver, United States and when he return to Chile in 1961 inaugurated the Department of Physical Medicine and Rehabilitation in the Clinical Hospital of the University of Chile. In 1964 began the training of residents. From then until the date the post title of Physical Medicine and Rehabilitation at the University of Chile is the only one that takes place in Chile, is a multicenter program has been accredited by the Chilean Association of Medical Schools (ASOFAMECH), the last opportunity in 2001.